Seasonal and Regional Dependence of Cloud-to-Ground Lightning Density and Return Stroke Peak Current over Thailand - Bandholnopparat, Kittanapat; Prikaen, Chanphen; Bunyatunma, Charud; Buddhakala, Moragote; Areerachakul, Nathaporn (Kalasin University Journal of Science Technology and Innovation, 2024)
Negative and Positive Cloud-to-Ground lightning flashes 67,921 events obtained by World Wide Lightning Location Network (WWLLN) between January 2017 and December 2019 were used to study the seasonal and regional dependence of CG flash density and return stroke peak current over Thailand. We found that the highest CG flash density occurs in eastern Thailand. The CG flash density over this area is higher than 50 flashes/square kilometers/year, especially between March and May, CG flash occurs 1.2 events every minute. However, over northern Thailand, the CG flash density is less than 5 flashes/square kilometers/year. It is also found that the return stroke peak current of CG lightning over Thailand varies from 10kA – 150kA with an average value of 61.1 kA.